Spondarthritis in the Triassic - Cisneros, Juan Carlos; Gomes Cabral, Uiara; de Beer, Frikkie; Damiani, Ross; Costa Fortier, Daniel (PLOS ONE, 2010)
Background The evidence of several forms of arthritis has been well documented in the fossil record. However, for pre-Cenozoic vertebrates, especially regarding reptiles, this record is rather scarce. In this work we present a case report of spondarthritis found in a vertebral series that belonged to a carnivorous archosaurian reptile from the Lower Triassic (∼245 million years old) of the South African Karoo. Methodology/Principal Findings Neutron tomography confirmed macroscopic data, revealing the ossification of the entire intervertebral disc space (both annulus fibrosus and nucleus pulposus), which supports the diagnosis of spondarthritis. Conclusions/Significance The presence of spondarthritis in the new specimen represents by far the earliest evidence of any form of arthritis in the fossil record. The present find is nearly 100 million years older than the previous oldest report of this pathology, based on a Late Jurassic dinosaur. Spondarthritis may have indirectly contributed to the death of the animal under study.